The main issues of Japanese Grand Strategies: past and present. (Journal of Oriental Studies, 2016)
The given article discusses the three main Japanese Grand Strategies. Also the article considers their general descriptions, historical significances, main goals and issues, theoretical and practical aspects.
Keywords: Japan; Yoshida doctrine; Koizumi doctrine; Abe doctrine; security; US-Japan relations